2016
DOI: 10.1136/esmoopen-2016-000068
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of the PRAME cancer immunotherapeutic in metastatic melanoma: results of a phase I dose escalation study

Abstract: PurposeThe PRAME tumour antigen is expressed in several tumour types but in few normal adult tissues. A dose-escalation phase I/II study (NCT01149343) assessed the safety, immunogenicity and clinical activity of the PRAME immunotherapeutic (recombinant PRAME protein (recPRAME) with the AS15 immunostimulant) in patients with advanced melanoma. Here, we report the phase I dose-escalation study segment.Patients and methodsPatients with stage IV PRAME-positive melanoma were enrolled to 3 consecutive cohorts to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 23 publications
1
50
0
3
Order By: Relevance
“…This CTA has been recently exploited as immunotarget in several vaccination trials, as full-length protein/peptides either alone or in combination with a different tumor antigen. In particular, PRAME-based immunotherapy had an acceptable safety profile and induced anti-PRAME-specific humoral and cellular immune responses in melanoma (44,45), as well as in non-small cell lung cancer, (46) prostate carcinoma and renal clear cell carcinoma. (45) The vaccination approaches using PRAME as target, however, clearly showed the difficulty of in vivo reactivating PRAME-specific CD8+ T cells, even after several consecutive rounds of administration of the immunogenic protein/peptides.…”
Section: Discussionmentioning
confidence: 99%
“…This CTA has been recently exploited as immunotarget in several vaccination trials, as full-length protein/peptides either alone or in combination with a different tumor antigen. In particular, PRAME-based immunotherapy had an acceptable safety profile and induced anti-PRAME-specific humoral and cellular immune responses in melanoma (44,45), as well as in non-small cell lung cancer, (46) prostate carcinoma and renal clear cell carcinoma. (45) The vaccination approaches using PRAME as target, however, clearly showed the difficulty of in vivo reactivating PRAME-specific CD8+ T cells, even after several consecutive rounds of administration of the immunogenic protein/peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have demonstrated the ability to generate ALY/HLA-A2-specific CD8 cytotoxic T lymphocytes (CTLs) that can specifically lyse PRAME + HLA-A2 + tumors and are reactive against primary leukemia (16)(17)(18), providing proof that this epitope is presented and can be targeted by immunotherapy. Clinical trials have also demonstrated that patients vaccinated against PRAME can develop PRAME-specific CTLs (19) and helper T cells (20). There are several major constraints to cellular and vaccine-based strategies.…”
Section: Pr20 Binds To Aly/hla-a2 Complexes In Prame/hla-a2-expressinmentioning
confidence: 99%
“…A number of consequences have been associated in patients with mutations in FH, including atypical hemolytic uremic syndrome (aHUS). [4][5][6] Although hemolytic uremic syndrome is characterized by thrombocytopenia, microangiopathic hemolytic anemia, and renal failure, aHUS has the added characteristic of not being associated with infection of Escherichia coli commonly found with HUS. aHUS results in damage to the microvasculature and endothelium because of rare genetic defects in FH.…”
Section: Michael Holinstat University Of Michiganmentioning
confidence: 99%
“…More elegantly, and specifically, might be to treat these patients with a more selective agent that would further direct the immune system to leukemia antigens PR1 or stem cell antigens such as WT1 or PRAME. This treatment might be a vaccine [2][3][4][5] or a T-cell receptor mimic antibody [6][7][8] or an engineered T cell.…”
mentioning
confidence: 99%